Microsatellite Instability in Stage II and III Colorectal Cancer: Patterns and Profile - Dubey, A P; Vishwanath, S; Nikhil, P; Rathore, Anvesh; Pathak, Abhishek; Kumar, Rakesh (Indian Journal of Medical and Paediatric Oncology, 2018)
Introduction: Around 80% of colorectal carcinoma are associated with chromosomal instability while rest of 20% are euploid, possessing defect in mismatch repair system (MMR) quintessential for surveillance and correction of errors introduced into microsatellites. The microsatellite instability (MSI) phenotype has three major clinical applications: prognosis of colorectal cancer (CRC), prediction of response to 5 fluorouracil, and irinotecan, and genetic assessment of Lynch syndrome. Materials and Methods: We analyzed all Stage II and Stage III colorectal cancer (CRC) for MSI, who presented at Army Hospital, Research and Referral, New Delhi, from January 2014 to December 2016. Although patients of Stage II CRC were taken throughout the study period, Stage III CRC was included in last 1½ years to compare the prevalence of MSI in these two subsets of patients. Results: 26.2% of Stage II and 11.3% of Stage III patients were found to be MSI-high (MSI-H) (P = 0.04). Nineteen (86%) of 22 MSI-H patients were below 30 years of age (P = 0.01). Of 22 MSI-H patients, 18 had right-sided tumors (P = 0.03) and only three patients had rectal tumors. Most common pattern of MSI-H tumors was loss of expression of MLH1 and PMS2, seen in 15 of 16 (88%) of Stage II and three of 6 (50%) of Stage III CRC (P = 0.04). Conclusion: We conclude higher prevalence of MSI-H tumors in Stage II, as compared to Stage III CRC, which was demonstrated slightly higher in our study compared to published literature. MSI-H tumors tend to occur with high frequency in younger population, with right-sided colonic tumors, histopathology characterized by mucinous subtype with high prevalence of tumor infiltrating lymphocytes. Loss of expression of two MMR proteins, namely, PMS2 and MLH1 has been identified in most of MSI-H patients of our study, of which 86% were <30 years of age. This is in contrast to observation in previous studies where loss of PMS2 and MLH1 proteins was observed in older (>70 years) patients with MSI-H tumors, and in younger patients, MSI-H status was associated with loss of MLH1, MSH2, and MSH6.
Keywords: Colorectal carcinoma; microsatellite instability; mismatch repair